62z-(45z+66)=

Simple and best practice solution for 62z-(45z+66)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 62z-(45z+66)= equation:


Simplifying
62z + -1(45z + 66) = 0

Reorder the terms:
62z + -1(66 + 45z) = 0
62z + (66 * -1 + 45z * -1) = 0
62z + (-66 + -45z) = 0

Reorder the terms:
-66 + 62z + -45z = 0

Combine like terms: 62z + -45z = 17z
-66 + 17z = 0

Solving
-66 + 17z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '66' to each side of the equation.
-66 + 66 + 17z = 0 + 66

Combine like terms: -66 + 66 = 0
0 + 17z = 0 + 66
17z = 0 + 66

Combine like terms: 0 + 66 = 66
17z = 66

Divide each side by '17'.
z = 3.882352941

Simplifying
z = 3.882352941

See similar equations:

| 2x^4+5x^3+5x^2+20x-12=0 | | (n-10)-7n=62 | | 1.3x+.4=1.7 | | X^2-400x+20000=0 | | 2x+7(x+3)=9(x-1)+5 | | 8s+15=0 | | 2n^2+13n-24= | | 2z^4-13z^2+36=0 | | 5(n-12)-7n=62 | | 5x-4(x-3)=16 | | 4(4e+1)=12 | | 2x+12-8x=9x-5 | | 5x+15=2x+q | | 3(n-10)-7n=62 | | -9y-39= | | .25+4=18 | | 11m-10m=9m | | 3(n-10)-7n=18 | | 12w-14w=6 | | n-5m=9 | | -2.4x-1=-2.2x+7 | | 5(n-10)-7n=62 | | 9+2=15 | | 17(x-7)=-8-9 | | 3x+4(3x+5)=25 | | 28=2h+18 | | 2x^2-23a+63= | | y+1=-2+7 | | 7(n-12)-52n=62 | | 3px=2q(r-5x)1 | | -2x-1x=-2 | | (2x^2+5-3)=0 |

Equations solver categories